Putusan Sela Dalam Perkara Perselisihan Hasil Pemilihan Umum - -, Bisariyadi (Jurnal Hukum & Pembangunan, 2019)
This paper departs from the presumption of common misconception in the use of terms as adopted in criminal and civil law. Interlocutory decision in the Constitutional Court has a different definition from criminal and civil law procedure. The difference is within the issue that is cover between the two. Interlocutory decisions in criminal and civil law deals only as far as admissability and jurisdiction, where in the Constitutional Court interlocutory decisions may actually related to the legal issues brought by the party. In addition, as the experience shows that interlocutory decisions are not only used as burden of proof but also part of the mechanism for imposing sanctions due to electoral fraud that negate the core value of democracy. It aims to rectify and redefine the conception of interlocutory decisions based on empirical experience of the Court in examining cases on eletoral disputes. Furthermore, this study will put forward a proposal in the context of revising the Court procedural law, specifically in regards to interlocutory decisions.